Local Cytotoxic Effects in Cobra Envenoming: A Pilot Study - Lin, Jing-Hua; Sung, Wang-Chou; Mu, Han-Wei; Hung, Dong-Zong (Toxins, 2022)
The cobra (genus Naja (N.)) is one of the most common venomous snakes. Due to its frequency and deadly complications of muscle paralysis, local necrosis, and chronic musculoskeletal disability, it should not be ignored. The pathology of devastating tissue destruction, even though specific antivenoms exist, is not fully clear. Here, we attempted to dig in envenomed tissues to study the clinical toxicology of cobra venom. Four cases of N. atra snake envenomation, in which the subjects developed advanced tissue injury, were involved in this study. We used enzyme-ligand sandwich immunoassay (ELISA) to assay the whole venom, cytotoxin A3 and short-chain neurotoxin (sNTX) in blood, bullae, wound discharge, and debrided tissue. We found that persistently high concentrations of venom and toxins, especially cytotoxin A3, were detected in bullae, wound discharge fluid and necrotic tissue of these patients even after large doses of specific antivenom treatment, and wide excision and advanced debridement could largely remove these toxins, lessen the size of necrosis, and promote wound healing. We also found that the point-of-care apparatus, ICT-Cobra kit, might be used to promptly monitor the wound condition and as one of the indicators of surgical intervention in cases of cobra envenomation in Taiwan.